Legal Product Justification on the Issue of E-Waste Export Restrictions - Fibrianti, Nurul (Law Research Review Quarterly, 2015)
Electronic waste or electronic waste is electronic waste that is used as commodities for trade between countries. So far, there is no consensus on whether the electronic waste can be used or updated for resale. The basic problem lies in law enforcement and the character of electronic waste law regulation at the international level.